1700 Expanding the phenotypic spectrum of progressive encephalomyelitis with rigidity and myoclonus syndrome (PERMS) associated with glycine receptor antibody: clinical and laboratory study of 20 patients. Issue 3 (9th February 2012) - Leite, M I; Waters, P; Carvajal, A; Woodhall, M; Vincent, A
Abstract : Glycine receptor antibodies (GlyR-Ab) were first detected in a patient with a very rare condition, progressive encephalomyelitis with rigidity and myoclonus (PERM; Hutchinson et al 2008), but a few recent reports suggest a wider clinical spectrum. Here we summarise clinical features of 20 patients with positive GlyR-Abs. The patients' ages ranged from 1.8 to 72 years. Fourteen were male and the one child was a girl. Most patients (85%) had a subacute or chronic/insidious presentation, often with acute exacerbations. These were mainly spasms, stiffness and rigidity of neck, trunk and limb muscles (>80%), and many also had myoclonus with excessive startle. Pyramidal signs (70%) and cranial-nerve involvement (65%) (oculomotor, trigeminal, facial and bulbar motor disturbance) were common. Cognitive deficits with encephalopathy/seizures, or sleep disturbances (50%), or autonomic dysfunction (45%) affected some patients. One third of patients needed admission to ICU for ventilation (muscle rigidity and spasms and/or autonomic dysfunction). Co-existing GAD antibodies were found in two patients. Few had CSF pleocytosis or oligoclonal bands; brain and cord MRI and EEG were normal or unspecific. Most patients responded well to immunotherapy, sometimes dramatically, but 3/20 patients died. Although not common, detection of GlyR-Abs can help in the diagnosis and treatment of a potentially severe and life-threatening condition.